Utilization of Local Plant as Fermented Feed and Supplements for Livestock in Sendang Village, Wonogiri District - Yeni Farida; Heru Sasongko; . Sugiyarto (Institut Pertanian Bogor, 2018)
Raising livestock has been used as sidejob by farmers in Sendang because of availability of feed is problem, especially in the dry season. The utilization of local plant is expected to reduce the proportion of the cost for animal feed cost. In addition, supplementation of feed or herbal medicine is expected to accelerate the growth of animals to increase farmers' profits. This program aimed to provided solutions for feed endurance as well as provided knowledge to farmers about the use of medicinal plants to accelerate the growth of livestock. This program consists of three stages as followed: socialization and counseling, fermentation and herbal weightlifting ration formulation training and then evaluation. This program conducted for 45 days. The result was farmer awareness of local feed potency in Sendang village, increasing of farmer understanding about fermentation and supplement ration, ration formulation utilized directly by participant. To support the sustainability of the program, team created modules, supervised and coordinated with the head of the farmer group.